Who Do Leaders Talk To? The Role of Workplace Friendships in Professional Discussion Networks and Burnout - Schutzmann, Réka; Soltész-Várhelyi, Klára; Kozák, Anna (European Journal of Mental Health, 2025)
Introduction: Quantitative and emotional demands pose risks to leaders’ mental health, while supportive workplace relationships may mitigate these effects. Aims: This study examined the relationship between the friendship-based composition of the professional core discussion networks (pCDNs), job demands, and burnout among Hungarian social care leaders, guided by the social ledger framework to capture both the supportive and burdensome aspects of workplace relationships. Methods: 547 Hungarian social care leaders were categorised into six groups based on their pCDN composition. Participants’ pCDNs were assessed by social network analysis methods, and the COPSOQ II questionnaire measured work-related psychological dimensions and burnout. ANCOVA analyses were conducted to compare burnout and job demands across groups. Results: Leaders whose pCDNs consisted exclusively of non-friends reported the highest levels of burnout, whereas those with a single friend exhibited the lowest. Emotional demands were highest among leaders with one-friend pCDN and lowest among those with non-friend pCDNs. Emotional demands were associated with burnout; however, this relationship was moderated by pCDN composition: Leaders with one-friend pCDN reported low levels of burnout, regardless of the emotional demands, whereas the burnout of leaders with non-friend pCDNs was high even at low emotional demand levels. Additionally, those with no pCDN showed a strong association between emotional demands and burnout. Conclusions: The composition of pCDNs is important for leaders’ mental health. While friendships within pCDNs may offer emotional protection, they could also introduce strain, emphasising the need to consider not only the existence but also the quality of workplace relationships.